Mobile VR application in 5G network - Jie LIU; Qingyang WANG; Yilin LIN (Dianxin kexue)
VR/AR/MR application scenarios were introduced,as well as the basic principle of VR system,the requirements for the bearer network and those problems concerning exiting mobile bearing were analyzed.With the introducing of 5G new architecture and new techniques,a solution was put forward and the application effect was analyzed,the application-enhanced enhancements brought by the solution was further analyzed,aiming at providing reference for VR application deployment in 5G network and setting up a demonstrative example for other innovative applications in 5G ecosystem.